Needs assessment of workplace English and Malaysian graduates’ english language competency - Sarudin, Isarji; Mohd Noor, Zainab; Zubairi, Ainol Madziah; Tunku Ahmad, Tunku Badariah; Nordin, Mohamad Sahari (IDOSI Publication, 2013)
Communication skills in English have been identified as essential workplace tools for success in business and have been correlated with career success and increased in financial rewards. Not with standing, there is a global concern regarding the widening gap between the communication skills in English of job applicants and the English language competency required for employment. This paper presents the findings of a study to investigate the importance of English competency for employment and employers’ needs for an English competency certification test. Data for the study were gathered from 295 companies representing 14 industry sectors using a 14-item survey questionnaire, focus group discussion and semi-structured interviews. The findings of the study indicate that English was the most important language for employment; English competency was assessed in the recruitment process by all industry sectors; and employers provided in-house training programs to enhance employees’ English language competency. It was also found that employers advocated the need for a valid, reliable, globally benchmarked and industry-driven English competency certification test for non-native speakers of English. The paper concludes that due to the competitiveness of the market environment, the test would provide the impetus for institutions of higher learning to adequately prepare graduates with employability skills associated with communication skills in English for the workplace.